Bilateral Ocular Leprosy An Effect By Erythema Nodusum Leprosum : A Case Report: Poster Presentation - Case Report - Resident - PETER SALMON; Monica Camilla Chandra; Elbetty Agustina br.Simanjuntak,MD; Ivonne Ramenusa, MD (Majalah Oftalmologi Indonesia, 2023)
Introduction : Leprosy or Hansen’s disease is an infection caused by Mycobacterium leprae that primarily affects the skin, the peripheral nerves and the eyes, causing chronic granulomatous inflammation. Case Illustration : We present a case of lepromatous leprosy with erythema nodosum leprosum of a 47 years old man with bilateral and asymmetrical ocular complications. One year ago patient consumed multidrug therapy for leprosy for one year but didn’t finish the medication. On the right eye diagnose with chronic anterior and intermediate uveitis, on the left eye with panuveitis. Best corrected visual acuity (BCVA) was 2/60 for right eye and light perception for left eye. Intraocular pressure were within normal limits. Madarosis and corneal hypoesthesia were found on both eyes. On the right eye was found cells, synechia anterior and posterior, iris pearls and vitreous haze. On the left eye was found plasmoid iridocyclitis and vitreous opacities from USG. Slit skin smear (SSS) result positif acid fast bacilli (AFB) dan granular. Patients were treated with multidrug therapy for leprosy, topical antibiotics, atropine and steroids, oral antibiotics and treatment from a dermatologist. Discussion : The diagnosis of lepromatous uveitis (LU) in this patient is made through skin tissue biopsy and ophthalmological examination. The effective management of ocular leprosy depends on early diagnosis and appropriate treatment. Hence it is imperative for ophthalmologist to recognize the ocular clinical signs associated with leprosy. Conclusion : Most blindness and impaired vision resulting from leprosy is preventable. A multidisciplinary approach is to be taken in order to improve the prognosis.